A System of Their Own: Records Creation and Recordkeeping in Canada’s Department of External Affairs in the 1920s - Shumilak, Anna (Archivaria, 2013)
This article explores aspects of the political-legal-constitutional context of Canada’s Department of External Affairs. Specifically, it traces some of the changes made to the department’s records creation and recordkeeping systems in the 1920s, initiated by an increased responsibility for the conduct and administration of Canada’s foreign affairs activities. Underlying this analysis is a recognition that by striving to understand the historical and organizational context of External Affairs, users and archivists are also able to achieve a more complete understanding of the records that were created at that time. In this way, the article contributes to a much broader archival discourse, which centres on encouraging the study of the history and context of archival records. RÉSUMÉ Cet article explore les aspects du contexte politique, légal et constitutionnel du ministère des Affaires étrangères du Canada. Spécifiquement, il trace des changements qui ont été apportés aux systèmes de création et de gestion de documents du ministère pendant les années 1920, mis en place suite à un accroissement des responsabilités dans la conduite et l’administration des activités des affaires étrangères du Canada. Soustendant cette analyse est la reconnaissance qu’en essayant de comprendre le contexte historique et organisationnel des Affaires étrangères, les utilisateurs de documents et les archivistes sont aussi mieux en mesure d’atteindre une compréhension plus complète des documents qui ont été créés à cette époque. Ainsi, cet article contribue à un discours archivistique beaucoup plus large, qui est centré sur l’incitation à étudier l’histoire et le contexte des documents d’archives.